Structural analysis of steel structures with non-symmetric members. (15th October 2021) - Sippel, Edward J.; Blum, Hannah B.
Highlights: More torsional restraint in a system improves agreement between analyses types. At lower loading, doubly symmetric response can agree with more detailed methods. Non-symmetric behavior was more impactful at higher loading and lead to variations. Doubly symmetric analyses fail prematurely with stability problems without warping. Ignoring non-symmetric properties can cause conservative and unconservative results. Abstract: Cold-formed steel components exist in a variety of structural systems including wall, floor, and roofing systems. A common feature of these cross sections is that they are often open and singly symmetric or point symmetric. While design requirements for these cross-sections account for the relevant effects resulting from their lack of symmetry, structural analysis programs do not always consider these effects. Engineers will use structural analysis programs to calculate the appropriate load sharing among members in the structural system. Accounting for the appropriate stiffness of each member and the related deformations is a vital component to determining the final distribution of bending moment, forces, and displacements. Many common structural analysis programs treat all sections as doubly symmetric without warping. Removing this assumption causes non-symmetric cross sections to exhibit nonplanar displacements and complicates the stability limits. The analysis of two structural systems composed of non-symmetric members was completed with varying member modeling assumptions utilizing multiple finite element software programs. A single channel portal frame was investigated that was subjected to simulated gravity load and wind loading with varying bracing support. Additionally, a roofing system with Z-section or channel purlins and channel bracing was investigated. The finite element analysis results were compared among the various modeling assumptions and existing experiments where available. It was observed that good agreement between the doubly symmetric and the more complex analyses was obtained in some instances, particularly when the members were loaded to low levels and highly constrained. However when loading is closer to the elastic limits and members can more freely move out-of-plane, the inclusion of non-symmetric section properties becomes a critical factor in determining an accurate response for both internal forces and displacements. The variations between these different analysis methods were found to be difficult to predict due to the cumulative effect of the competing mechanical behaviors that could result in either conservative or unconservative responses when ignoring non-symmetric behavior.